Penerapan Laporan Keuangan Berbasis SAK EMKM pada UMKM Amplang NA - B1031141031, Novilia Hidayanti (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2018)
One way that can be done to support national development is through Micro, Small and Medium Enterprises (MSMEs). This study aims to determine the application of financial statements on Amplang NA, knowing the application of SAK EMKM-based financial statements on Amplang NA and knowing the constraints in the implementation of SAK EMKM-based financial statements on Amplang NA. This is a qualitative research and uses descriptive methods. Data sources used in this study are primary data which are the data obtained through interviews conducted by researchers on owners and administrators and through direct observation on Amplang NA. Besides, secondary data obtained through documentary evidence owned by Amplang NA. The results of this study indicate that there are several elements of SAK EMKM which are still not implemented by Amplang NA. Financial statement in the year of 2017 that were previously only limited to income and expenditure, are now in accordance with SAK EMKM. There is a major obstacle faced in implementing SAK EMKM, namely the lack of information regarding SAK EMKM that applies specifically to MSMEs.Keywords: MSMEs, SAK EMKM, Indonesian Accountants Association, Financial StatementsDAFTAR PUSTAKAIkatan Akuntansi Indonesia. (2016). Exposure Draft Standar Akuntansi Keuangan Entitas Mikro, Kecil, dan Menengah. Jakarta: IAIIkatan Akuntansi Indonesia. (2016). Standar Akuntansi Keuangan Entitas Mikro, Kecil, dan Menengah. Jakarta: IAI.Indriatoro, N., & Supomo, B. (2016). Metodologi Penelitian Bisnis Untuk Akuntansi Dan Manajemen. Yogyakarta: BPFE-YogyakartaNingrum, T.D. (2018). Implementasi SAK EMKM Pada Usaha Kecil dan Menengah (UKM) Tiara Catering. Skripsi. Universitas Tanjungpura Pontianak.Pedoman Penulisan Karya Akhir. (2016). Pontianak: Fakultas Ekonomi Dan Bisnis Universitas Tanjungpura.Pratiwi, A.A., Sondakh, J.J., & Kalangi, L. (2014). Analisis Penerapan SAK ETAP Pada Penyajian Laporan Keuangan PT. Nichindo Manado Suisan. Jurnal EMBA, Vol.2 No.3, 254-265. Universitas Sam Ratulangi Manado.Primayudia, D. (2017). Penyusunan Laporan Keuangan Usaha Budidaya Ikan Nila di Keramba â€œSejahteraâ€ Berbasis SAK EMKM. Skripsi. Universitas Tanjungpura Pontianak.Rahmawati, T., & Puspasari, O.R. (2017). Implementasi SAK ETAP dan Kualitas Laporan Keuangan Terkait Akses Modal Perbankan. Jurnal Kajian Akuntansi, Vol.1 No.1, 49-62. Universitas Kuningan.Ramadhani, E. (2017). Analisis Penerapan SAK EMKM dalam Laporan Keuangan Toko Abang Apple. Skripsi. Universitas Tanjungpura Pontianak.Rudiantoro, R., & Siregar, S.V. (2012). Kualitas Laporan Keuangan UMKM Serta Implementasi SAK ETAP. Jurnal Akuntansi dan Keuangan Indonesia, Vol.9 No.1, 1-21. Universitas Indonesia.Shonhadji, N., dkk. (2017). Penerapan Penyusunan Laporan Keuangan Pada Usaha Kecil Menengah Berdasarkan SAK EMKM di Surabaya. Seminar Nasional Hasil Pengabdian kepada Masyarakat (SENIAS) 2017, 130-136. Universitas Islam Madura.Singal, R.A., & Pinatik, S. (2015). Evaluasi Penyusunan Laporan Laba Rugi dan Neraca Berdasarkan SAK ETAP Pada PT. Karunia Multiguna Abadi. Jurnal EMBA, Vol.3 No.4, 395-403. Universitas Sam Ratulangi Manado.Sirait, P. (2014). Pelaporan dan Laporan Keuangan. Yogyakarta: Graha Ilmu.Siswono, E. (2013). Penerapan Penyusunan Laporan Keuangan Pada Usaha Kecil Menengah Berbasis Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik (Studi Kasus UKM Brebes Fried Chicken). Universitas Dian Nuswantoro Semarang.Sodikin, S.S., & B.A Riyono. (2014). Akuntansi Pengantar 1 Edisi 9. Yogyakarta: UPP STIM YKPN.Sugiyono. (2014). Metode Penelitian Manajemen. Bandung: Alfabeta.Sugiyono. (2014). Metode Penelitian Pendidikan Pendekatan Kuantitatif, Kualitatif, dan R&D. Bandung: Alfabeta.Sugiyono. (2015). Cara Mudah Menyusun: Skripsi, Tesis, dan Disertasi. Bandung: Alfabeta.Sumarsan, T. (2013). Akuntansi Dasar dan Aplikasi Dalam Bisnis Versi IFRS Jilid 1. Jakarta: Indeks.Suwardjono. (2014). Teori Akuntansi Perekayasaan Pelaporan Keuangan. Edisi Ketiga. Yogyakarta: BPFE-Yogyakarta.Umar, H. (2014). Metode Penelitian Untuk Skripsi dan Tesis Bisnis. Jakarta: Rajawali Pers.Undang-Undang No. 20 Tahun 2008 Tentang Usaha Mikro, Kecil dan Menengah. http://www.hukumonline.com/pusatdata/download/fl56047/node/28029Warsadi, A.K., Herawati, N.T., & Julianto, I.P. (2017). Penerapan Penyusunan Laporan Keuangan pada Usaha Kecil Menengah Berbasis Standar Akuntansi Keuangan Entitas Mikro, Kecil, dan Menengah pada PT. Mama Jaya. e-Journal S1 Ak, Vol.8 No.2. Universitas Pendidikan Ganesha.